Leadership Development Program for Indonesia Government: Literature Review - Minaldi, Idham; Soeling, Pantius Drahen (International Journal Labs, 2025)
Indonesia’s public-sector leadership needs programs that combine essential skills with local cultural norms. Using a SALSA-guided systematic review of ten empirical studies, the identified five themes: building strategic, communication, and adaptive competencies; integrating cultural; delivering via blended workshops, e-learning, and action projects; evaluating through Kirkpatrick’s four levels; and aligning with institutional strategy. Effective programs employ culturally tailored, blended formats, rigorous multi-level assessment, and linkage to talent pipelines. Future research should measure long-term leadership outcomes, explore cultural influences in depth, and test methods for enhancing learning agility among government leaders.